THE EFFECT OF ASSERTIVE BEHAVIOR AND SELF-DISCLOSURE ON MATHEMATICAL PROBLEM-SOLVING ABILITY (SURVEY AT SMP NEGERI IN NORTH JAKARTA) - Wisman (ZILLZELL MEDIA PRIMA, 2023)
Objectives of the study: (1) Knowing the direct influence of assertive behavior on the ability to solve mathematical problems in public junior high school students in North Jakarta. (2) Knowing the direct effect of self-disclosure on the ability to solve mathematical problems in public junior high school students in North Jakarta. (3) Knowing the direct influence of assertive behavior on self-disclosure in public junior high school students in North Jakarta. (4) Knowing the indirect influence of assertive behavior through self-disclosure on the ability to solve mathematical problems in public junior high school students in North Jakarta. The method used in this study is the survey method. This study used a survey study. Test the hypothesis using path analysis. The results concluded: (1) There is a significant direct influence of assertive behavior on solving mathematics problems of public junior high school students in North Jakarta. This is evidenced by the acquisition of Sig. = 0.000 < 0.05 and (2) There is a significant direct influence of self-disclosure on solving mathematics problems of public junior high school students in North Jakarta. This is evidenced by the acquisition of Sig. = 0.038 < 0.05 and . (3) There is a significant direct influence of assertive behavior on the self-disclosure of public junior high school students in North Jakarta. This is evidenced by the acquisition of Sig. = 0.000 < 0.05 and . (4) There is a significant indirect influence of assertive behavior through self-disclosure on the mathematical problem-solving ability of public junior high school students in North Jakarta. This can be proven by the value,